Intraorgan use of Hemoblock for prevention and arrest of bleedings in endoscopic excision of gastric polyps - S. G. Tereshchenko; A. V. Plotkin; L. V. Mecheva (Неотложная медицинская помощь, 2019)
INTRODUCTION Bleedings after endoscopic removal of gastric polyps continue to be a relevant issue. A technique has been developed for infltrating the base of polyps with a new hemostatic agent Hemoblock to prevent bleedings during polypectomy. The purpose of this study was to assess the effectiveness of this technique.MATERIALS AND METHODS We present the results of the use of Hemoblock in 63 patients with 129 removed polyps. The results were compared with data in the control group, where 267 polyps were removed in 142 patients. In the control group, 0.9% sodium chloride solution, 5% aminocaproic acid solution were used for submucosa injection. We also compared the effectiveness of endoscopic hemostasis for bleeding that occurred after the removal of polyps in both groups. In the main group, hemostasis was performed by irrigation and puncturing using Hemoblock. In the control group the injection method (0.9% sodium chloride solution, 5% aminocaproic acid solution) and electrocoagulation were performed.RESULTS The study showed that the use of Hemoblock during endoscopic removal of polyps for infltration of their base provided a more effective prevention of bleeding, and with the development of bleeding from a thermal defect after polypectomy, the use of irrigation/puncturing of the same drug provides reliable hemostasis.CONCLUSION The use of hemostatic agent Hemoblock in the endoscopic removal of gastric polyps provides prevention of bleeding and radical intervention. With the development of bleeding after polypectomy, irrigation/puncturing hemostatic agent Hemoblock allows to achieve reliable hemostasis.